Effect of using HEART score in patients with chest pain at the emergency department of University Clinical Centre of the Republic of Srpska - Bojan Stanetić; Nenad Jaćimović; Šemsudin Porčić (Биомедицинска истраживања, 2021)
Introduction: Recent data show that 1/5 of patients with chest pain in the emergency room (ER) have an acute coronary syndrome that requires admission and treatment. Current guidelines have endorsed the HEART score for admission, observation or discharge in individual patients. We aimed to assess performance of the HEART score at the University Clinical Centre of the Republic of Srpska. Methods: Between March 1 and March 31, 2019, all patients with chest pain who presented at ER were evaluated. The HEART score for each patient was calculated, and patients were stratified based on the HEART score recommendation, i.e. low-, intermediate-and high-risk. Patients were followed 6 weeks for major adverse cardiac events (MACE). Results: Out of a total of 144 included patients, 23 had low-risk (0-3) HEART scores, while 73 and 48 patients had intermediate-risk (4-6) and high-risk (7-10) HEART scores, respectively. The discordance among intuitive judgments by clinicians and the HEART score advice became typically obtrusive in patients with excessive (7-10) HEART score rankings: 25 out of 48 (52.1%) patients had been discharged, while the remaining 22 patients had been admitted and 1 person was observed. In population with HEART score rankings 4-6, MACE became recognized in 1/73 (1.4%) while in patients with excessive HEART score rankings (values 7-10), MACE befell in 5/48 (10.4%). Only one patient who was discharged experienced MACE. The ROC analysis of the HEART score revealed a value of 0.78, suggesting a good performance in discriminating between low-and high-risk patients. Conclusion: Discordance between clinical decision and HEART score recommendation was not associated with severe clinical consequences.
Keywords: Heart score; emergency room; chest pain